2014
DOI: 10.18632/genesandcancer.29
|View full text |Cite
|
Sign up to set email alerts
|

Mirk kinase inhibition blocks the in vivo growth of pancreatic cancer cells

Abstract: The Mirk/dyrk1B gene is upregulated and sometimes amplified in pancreatic ductal carcinomas. In poor microenvironmental conditions Mirk mediates cell survival by maintaining cancer cells in a largely quiescent, noncycling state and by decreasing toxic ROS levels through maintaining expression of a series of antioxidant genes. Premature entry into cycle, increased ROS levels, DNA damage, and apoptosis follow Mirk kinase depletion or inhibition. Mirk kinase inhibitor EHT5372 treated Panc1 spheroids lost quiescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 37 publications
3
24
0
Order By: Relevance
“…Using SMO-inhibitor resistant pancreatic cancer cells we also confirm a previous report showing that DYRK1B targeting in pancreatic cancer cells has pronounced therapeutic efficacy in vitro and in vivo , though the molecular mechanisms including the link to HH/GLI signaling remained unidentified in this study [ 56 ]. In the present study we show that interfering with DYRK1B dramatically impairs SMO-independent GLI1 expression in RAS mutant pancreatic cancer cells and phenocopies the anti-tumorigenic effect of GLI1 targeting [ 16 ].…”
Section: Discussionsupporting
confidence: 88%
“…Using SMO-inhibitor resistant pancreatic cancer cells we also confirm a previous report showing that DYRK1B targeting in pancreatic cancer cells has pronounced therapeutic efficacy in vitro and in vivo , though the molecular mechanisms including the link to HH/GLI signaling remained unidentified in this study [ 56 ]. In the present study we show that interfering with DYRK1B dramatically impairs SMO-independent GLI1 expression in RAS mutant pancreatic cancer cells and phenocopies the anti-tumorigenic effect of GLI1 targeting [ 16 ].…”
Section: Discussionsupporting
confidence: 88%
“…Kaplan-Meier survival curve analysis showed that well-differentiated liposarcoma patients have a better prognosis than other pathology subtypes [ 35 ]. These findings validate previous reports that amplified expression of DYRK1B is involved in the progression of certain cancers and associated with poor prognosis [ 36 40 ]. We then investigated the function roles of DYRK1B in liposarcoma cells.…”
Section: Discussionsupporting
confidence: 92%
“…DYRK1B facilitates skeletal myoblast differentiation and survival by mediating cell cycle arrested in G 0 phase and exerting anti-apoptotic effect [ 21 , 22 ]. More importantly, DYRK1B is overexpressed and highly activated in many types of solid tumors, including pancreatic, lung, ovarian, colon cancer, rhabdomyosarcoma and osteosarcoma [ 23 28 ]. On the other hand, emerging insights into DYRK1B promotion adipogenesis and involvement in metabolic syndrome suggest that DYRK1B may potentially relevant to fat cell malignancy [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the arguments put forward here raise the possibility that androgens elicit anti-proliferative signals in human cancers bearing oncogenic Ras mutations through activation of DYRK 1B. Noteworthy, DYRK 1B is an active kinase in various human cancers and regulates Ras-driven transformation and tumor progression ( 38 40 ). Thus, by activating DYRK 1B kinase, androgen/AR axis might restrain Ras-driven transformation.…”
Section: Androgen Signaling In Stromal Cellsmentioning
confidence: 91%